Rahasia Finlandia Menjadi Pendidikan Terbaik di Dunia - Jajang Bahrul Ulum; Agus Faisal Asyha (CV. Rumoh Aceh Publishing, 2026)
This study aims to analyze the factors behind Finland's success as one of the countries with the best education systems in the world. The research was conducted through a library research approach by utilizing various secondary data sources, including books, scientific journals, research articles, and official documents related to the Finnish education system. The study employed a qualitative approach with data collection through documentation techniques and descriptive qualitative data analysis. The findings reveal that the success of Finland's education system is supported by several factors, including continuous educational reforms, an educational philosophy emphasizing equality and student potential development, strong community support for education, government policies ensuring equal access to education, highly qualified teachers, and a competency-based curriculum focused on 21st-century skills. Furthermore, student-centered learning and a supportive learning environment significantly contribute to the high quality of education in Finland. The study concludes that Finland's educational success is the result of strong collaboration among the government, schools, families, and society in creating a high-quality, inclusive, and sustainable education system.